Pragmatisierung der Syntax - Żebrowska, Ewa (Studia Germanica Posnaniensia, 2018)
This article presents the role of modeling in linguistics. It is used to recognize regularities in the language. Special emphasis was put on the linguistic analysis universal model of Józef Darski. The author of the paper has successfully applied it to the study of morphology and syntax at the dialectal level.